التقاضي امام المحاكم الادارية الدولية - ريم سعايدية; هشام نحنوح (My University, 2020)
Summary The international staff member enjoys many privileges and rights that make him distinct from other employees of international organizations, the international administrative tribunals have been established as a judicial guarantee to resolve any dispute between the international staff member and his organization, as he enjoys the capacity to sue before these courts. He was granted all legal and even administrative means to claim his right, by filing his case and appealing against the judgments; so the procedure for litigation before the international administrative tribunals was distinct from litigation before the ordinary administrative courts at the national level. .................... ﺍﻟﻤﻠﺨﺺ ﻳﺘﻤﺘﻊ ﺍﻟﻤﻮﻅﻒ ﺍﻟﺪﻭﻟﻲ ﺑﺎﻟﻜﺜﻴﺮ ﻣﻦ ﺍﻻﻣﺘﻴﺎﺯﺍﺕ ﻭﺍﻟﺤﻘﻮﻕ ﺍﻟﺘﻲ ﺗﺠﻌﻠﻪ ﻳﺘﻤﻴﺰ ﻋﻦ ﻏﻴﺮﻩ ﻣﻦ ﺍﻟﻤﺴﺘﺨﺪﻣﻴﻦ ﺍﻟﺘﺎﺑﻌﻴﻦ ﻟﻠﻤﻨﻈﻤﺎﺕ ﺍﻟﺪﻭﻟﻴﺔ، ﻭ ﻗﺪ ﺃُﻧﺸﺌﺖ ﺍﻟﻤﺤﺎﻛﻢ ﺍﻹﺩﺍﺭﻳﺔ ﺍﻟﺪﻭﻟﻴﺔ ﻛﻀﻤﺎﻧﺔ ﻗﻀﺎﺋﻴﺔ ﻟﻔﺾ ﺃﻱ ﻧﺰﺍﻉ ﻳﺜﻮﺭ ﺑﻴﻦ ﺍﻟﻤﻮﻅﻒ ﺍﻟﺪﻭﻟﻲ ﻭ ﺍﻟﻤﻨﻈﻤﺔ ﺍﻟﺘﺎﺑﻊ ﻟﻬﺎ، ﻛﻮﻧﻪ ﻳﺘﻤﺘﻊ ﺑﺄﻫﻠﻴﺔ ﺍﻟﺘﻘﺎﺿﻲ ﺃﻣﺎﻡ ﻫﺬﻩ ﺍﻟﻤﺤﺎﻛﻢ، ﺣﻴﺚ ﻣﻨﺤﺖ ﻟﻪ ﺟﻤﻴﻊ ﺍﻟﻮﺳﺎﺋﻞ ﺍﻟﻘﺎﻧﻮﻧﻴﺔ ﻭﺣﺘﻰ ﺍﻹﺩﺍﺭﻳﺔ ﻟﻠﻤﻄﺎﻟﺒﺔ ﺑﺤﻘﻪ، ﺑﺮﻓﻊ ﺩﻋﻮﺍﻩ ﺃﻣﺎﻣﻬﺎ ﻭﺍﺳﺘﺌﻨﺎﻓﻪ ﻟﻸﺣﻜﺎﻡ ﺍﻟﺼﺎﺩﺭﺓ ﻋﻨﻬﺎ ﻓﻲ ﺣﻘﻪ؛ ﻣﻊ ﺗﻤﻴّﺰ ﺇﺟﺮﺍءﺍﺕ ﺍﻟﺘﻘﺎﺿﻲ ﺃﻣﺎﻡ ﺍﻟﻤﺤﺎﻛﻢ ﺍﻹﺩﺍﺭﻳﺔ ﺍﻟﺪﻭﻟﻴﺔ ﻋﻦ ﺍﻟﺘﻘﺎﺿﻲ ﺃﻣﺎﻡ ﺍﻟﻤﺤﺎﻛﻢ ﺍﻹﺩﺍﺭﻳﺔ ﺍﻟﻌﺎﺩﻳﺔ ﻋﻠﻰ ﺍﻟﺼﻌﻴﺪ ﺍﻟﻮﻁﻨﻲ. ..... Résumé Le membre du personnel international jouit de nombreux privilèges et droits qui le distinguent des autres employés des organisations internationales, les tribunaux administratifs internationaux ont été établis comme garantie judiciaire pour régler tout différend entre l’employé international et son organisation, car il jouit de la capacité d’intenter des poursuites devant ces tribunaux. Il s’est vu accorder tous les moyens légaux et même administratifs pour revendiquer son droit, en déposant son dossier et en faisant appel contre les jugements; donc la procédure de contentieux devant les tribunaux administratifs internationaux était distincte de celle devant les tribunaux nationaux.